Odpowiedź :
a1= -2 i q = 2
a2=-2*2=-4
a3=-4*2=-8
a4=-8*2=-16
a5=-16*2=-32
a1 =3 i g = 0,5
a2=3* 1/2=3/2
a3=3/2* 1/2=3/4
a4=3/4* 1/2=3/8
a5=3/8 *1/2= 3/16
a2=-2*2=-4
a3=-4*2=-8
a4=-8*2=-16
a5=-16*2=-32
a1 =3 i g = 0,5
a2=3* 1/2=3/2
a3=3/2* 1/2=3/4
a4=3/4* 1/2=3/8
a5=3/8 *1/2= 3/16
a) a2=a1*q=-2*2=-4
a3=a2*q=-4*2=-8
a4=a3*q=-8*2=-16
a5=a4*q=-16*2=-32
b) a2=a1*q=3*0,5=1,5
a3=a2*q=1,5*0,5=0,75
a4=a3*q=0,75*0,5=0,375
a5=a4*q=0,375*0,5=0,1875
a3=a2*q=-4*2=-8
a4=a3*q=-8*2=-16
a5=a4*q=-16*2=-32
b) a2=a1*q=3*0,5=1,5
a3=a2*q=1,5*0,5=0,75
a4=a3*q=0,75*0,5=0,375
a5=a4*q=0,375*0,5=0,1875